Prototyping Connected Devices for the Internet of Things - Hodges, Steve; Taylor, Stuart; Villar, Nicolas; Scott, James; Bial, Dominik; Fischer, Patrick Tobias (IEEE Computer, 2013)
Tools like Microsoft .NET Gadgeteer offer the ability to quickly prototype, test, and deploy connected devices, providing a key element that will accelerate our understanding of the challenges in realizing the Internet of Things vision.